How should radiation exposure be handled in fluoroscopy‐guided endoscopic procedures in the field of gastroenterology?. Issue 5 (12th January 2022) - Takenaka, Mamoru; Hosono, Makoto; Hayashi, Shiro; Nishida, Tsutomu; Kudo, Masatoshi
Abstract : Fluoroscopy‐guided endoscopic procedures (FGEPs) are rapidly gaining popularity in the field of gastroenterology. Radiation is a well‐known health hazard. Gastroenterologists who perform FGEPs are required to protect themselves, patients, as well as nurses and radiologists engaged in examinations from radiation exposure. To achieve this, all gastroenterologists must first understand and adhere to the International Commission on Radiological Protection Publication. In particular, it is necessary to understand the three principles of radiation protection (Justification, Optimization, and Dose Limits), the As Low As Reasonably Achievable principle, and the Diagnostic Reference Levels (DRLs) according to them. This review will mainly explain the three principles of radiation exposure protection, DRLs, and occupational radiological protection in interventional procedures while introducing related findings. Gastroenterologists must gain knowledge of radiation exposure protection and keep it updated.